A study on solid waste management at Universiti Malaysia Pahang (UPM), Gambang Campus - Nurul Hana, Ishak (2018)
Nowadays, the population is increasing and this increase contributed to problems in various sectors and no exception to the environment if not controlled properly. All types of objects generated from unused resources will be classified as waste. Institutions are also one of the sources to generate residuals. This area of study was at three cafeteria at Universiti Malaysia Pahang Campus Gambang that are Chemical Cafeteria, Kolej Kediaman 1(KK1) and 3(KK3) Cafeteria, and Kolej Kediaman 4(KK4) Cafeteria. This study was conducted to study and determine the composition of solid waste. This study also to obtain data on solid waste generated in the institution, and also the generation of the factors that influence the rate of solid waste generation. The solid waste that has been collected has been dried and weight was taken based on the composition of food waste, paper, glass, aluminium and others. In addition, there are approximately ten-question questionnaire was distributed to 300 respondents including students, staff and workers in the Universiti Malaysia Pahang. The questionnaire was aimed at obtaining information, opinions and views from the public on the awareness of solid waste. At the end of data collection, all data will be analyzed using the statistical method and the results of the analysis will be evaluated, discussed and summarized. According to this study, the results of solid waste generated during the semester break for the seven consecutive days in Chemical Cafeteria was 7kg /week while for KK1 & KK3 Cafeteria was 5.15kg /week while for KK4 Cafeteria was 7.85kg /week. For the amount of solid waste generated during the semester is carried out in the Chemistry Cafeteria was 38.3kg /week, while the cafeteria KK1 & KK3 was 64.7kg /week for the Cafeteria and KK4 was 83.2kg /week. The composition of food waste shows the highest value compared to other compositions. Other factors that affect solid waste in the study are because the area is filled with students, staff and other workers eating at the cafeteria provided at Universiti Malaysia Pahang Campus Gambang.